2004
DOI: 10.1023/b:aibe.0000044072.71361.b3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Perceptions of HIV Risk Among Adolescents in KwaZulu-Natal

Abstract: Risk perception has been theorized to be an important antecedent for adopting protective behavior. It is a key construct of research applying the Health Belief Model and other behavior change models. In relation to HIV, risk perception is an indicator of perceived susceptibility to infection, a measure for one's understanding of AIDS transmission as well as willingness to consider behavioral changes. However, there remains much we do not know about what drives risk perception, especially among youth. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 30 publications
8
76
0
Order By: Relevance
“…Risk perception was measured as an ordinal variable with four categories that were dummy coded; no risk was the reference category, compared with responses of small, moderate or great risk. Following examples set in research in South Africa, [26][27][28] we measured participants' perception of the seriousness of AIDS by their reports of whether they personally knew someone who had died of AIDS, with "yes" and "don't know" dummy coded against the reference category, "no. "…”
Section: Factors Influencing the Timing Of First Sexual Intercourse Imentioning
confidence: 99%
See 1 more Smart Citation
“…Risk perception was measured as an ordinal variable with four categories that were dummy coded; no risk was the reference category, compared with responses of small, moderate or great risk. Following examples set in research in South Africa, [26][27][28] we measured participants' perception of the seriousness of AIDS by their reports of whether they personally knew someone who had died of AIDS, with "yes" and "don't know" dummy coded against the reference category, "no. "…”
Section: Factors Influencing the Timing Of First Sexual Intercourse Imentioning
confidence: 99%
“…12,16,17,20,21 Although these factors may motivate youth to engage in sexual activity, several models have theorized that the perceptions that AIDS is serious and that one is at risk of acquiring HIV can motivate individuals to adopt such riskreducing behaviors as delaying sexual debut, avoiding sexual activity or using condoms. [22][23][24][25] Evidence supporting these theories has been found in several South African studies [26][27][28] in which delayed sexual debut was associated with having known someone who had died of AIDS and perceiving one's own risk of becoming infected as high.…”
mentioning
confidence: 93%
“…Many adolescents are unaware of what constitutes risky sexual behaviour (Barden-O'Fallon, deGraft-Johnson, Bisika, Sulzbach, Benson & Tsui 2004;Macintyre, Rutenberg & Brown 2004;Pettifor, Rees, Steffenson, Hlongwa-Madikizela, MacPhail, Vermaak, et al 2004;Sarker, Milkowski, Slanger, Gondos, Sanou, Kouyate, et al 2005). Furthermore, most of the adolescents living with HIV do not know they are infected (UNAIDS 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that young South Africans often perceive their risk of HIV infection to be low, even if they engage in sexual risk behaviors (Macintyre et al, 2004;Kenyon et al, 2010a;Fraser-Hurt et al, 2011), which may reflect youthful optimism and feelings of invulnerability (Moore and Rosenthal, 1991;Macintyre et al, 2004). But studies have found that young South Africans have at least moderate levels of knowledge about the sexual transmission of HIV Shisana et al, 2009;Fraser-Hurt et al, 2011), and in keeping with health behavior models, studies using longitudinal data have found that South African youth with higher levels of self-perceived risk have lower odds of subsequently engaging in some sexual risk behaviors, such as first sex Tenkorang et al, 2009;.…”
Section: Hiv Risk Perceptionsmentioning
confidence: 99%
“…In addition to sexual risk behaviors, knowing someone with HIV may be important for HIV risk perceptions; experiential theory (Macintyre et al, 2004) suggests young people may have higher HIV risk perceptions at one point in time or may be more likely to increase their HIV risk perceptions over time if they know someone who has HIV. Little attention has been paid to these possibilities, although there is some evidence that knowing someone who died of AIDS is associated with higher HIV risk perceptions Kenyon et al, 2010a).…”
Section: Hiv Risk Perceptionsmentioning
confidence: 99%